Meningkatkan Keputusan Pembelian Melalui Inovasi Produk, Kualitas Produk dan Citra Merek di Mixue Yogyakarta - Setiawan, Arif Wahyu; Fadhilah, Muinah; Hutami, Lusia Tria Hatmanti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine the influence of product innovation, product quality, and brand image on purchasing decisions. This research is quantitative by taking 108 samples on Mixue consumers in Yogyakarta City. Sampling is carried out by non-probability methods and sampling techniques, namely purposive sampling. Data collection is carried out through sending questionnaire links sent online to respondents. Data analysis by using IBM SPSS applications. The results of this study showed that the product innovation variable (X1) did not have a significant positive effect on purchasing decisions (Y) with a value of 0.105. Then the product quality variable (X2) has a significant positive effect on purchasing decisions (Y) with a value of 0.000. The product innovation variable (X1) has a significant positive effect on brand image (Z) with a value of 0.001. Furthermore, the product quality variable (X2) has a significant positive effect on brand image (Z) with a value of 0.000. And the brand image variable (Z) has a significant positive effect on purchasing decisions (Y) with a value of 0.002. In addition, the results of the study also show that brand image can act as an intervening variable of the influence of product innovation and product quality on the purchasing decisions of Mixue consumers in Yogyakarta City. Keywords: Product Innovation; Product Quality; Brand Image; Purchasing Decision